Enhancing the Capacity of Prospective Young Entrepreneurs in Schools through Financial Literacy Training and the Utilization of Artificial Intelligence - Sitti Hajerah Hasyim; Hajar Dewantara; Andika Isma; Hasisa Haruna; Andi Anggi Kemalasari (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
The rapid development of digital technology and artificial intelligence (AI) has significantly transformed education and entrepreneurship. However, many young school entrepreneurs still face limitations in financial literacy, technological understanding, and the use of data to support business decision-making. These conditions create challenges in equipping them with adaptive and innovative entrepreneurial competencies in the digital era. This community service program aims to enhance the capacity of young prospective entrepreneurs through financial literacy training and the utilization of artificial intelligence. The implementation method consisted of three main stages: preparation, implementation, and evaluation. The preparation stage included initial observations, the development of training modules, and the design of evaluation instruments. The implementation stage involved financial literacy training and AI-based training, particularly in business simulation and data visualization. Evaluation was carried out using participant satisfaction surveys as well as pre-test and post-test assessments to measure improvements in knowledge and skills. The results indicated a significant increase in participants’ understanding of financial literacy, business budgeting, AI concepts, and data visualization skills. Participant satisfaction surveys revealed that most participants expressed satisfaction and high appreciation for the training materials and delivery methods. This program successfully addressed the identified problems and contributed to preparing inclusive, adaptive, and competitive young entrepreneurs in the era of digital transformation.